Ten years of implementation outcomes research: a scoping review - Enola K. Proctor; Alicia C. Bunger; Rebecca Lengnick-Hall; Donald R. Gerke; Jared K. Martin; Rebecca J. Phillips; Julia C. Swanson (Implementation Science, 2023)
Abstract Background Proctor and colleagues’ 2011 paper proposed a taxonomy of eight implementation outcomes and challenged the field to address a research agenda focused on conceptualization, measurement, and theory building. Ten years later, this paper maps the field’s progress in implementation outcomes research. This scoping review describes how each implementation outcome has been studied, research designs and methods used, and the contexts and settings represented in the current literature. We also describe the role of implementation outcomes in relation to implementation strategies and other outcomes. Methods Arksey and O’Malley’s framework for conducting scoping reviews guided our methods. Using forward citation tracing, we identified all literature citing the 2011 paper. We conducted our search in the Web of Science (WOS) database and added citation alerts sent to the first author from the publisher for a 6-month period coinciding with the WOS citation search. This produced 1346 titles and abstracts. Initial abstract screening yielded 480 manuscripts, and full-text review yielded 400 manuscripts that met inclusion criteria (empirical assessment of at least one implementation outcome). Results Slightly more than half (52.1%) of included manuscripts examined acceptability. Fidelity (39.3%), feasibility (38.6%), adoption (26.5%), and appropriateness (21.8%) were also commonly examined. Penetration (16.0%), sustainability (15.8%), and cost (7.8%) were less frequently examined. Thirty-two manuscripts examined implementation outcomes not included in the original taxonomy. Most studies took place in healthcare (45.8%) or behavioral health (22.5%) organizations. Two-thirds used observational designs. We found little evidence of progress in testing the relationships between implementation strategies and implementation outcomes, leaving us ill-prepared to know how to achieve implementation success. Moreover, few studies tested the impact of implementation outcomes on other important outcome types, such as service systems and improved individual or population health. Conclusions Our review presents a comprehensive snapshot of the research questions being addressed by existing implementation outcomes literature and reveals the need for rigorous, analytic research and tests of strategies for attaining implementation outcomes in the next 10 years of outcomes research.